Internal Auditing and Financial Performance of Organization a Case of Mukono District Local Government - Bridget Aber (Uganda Christian University, 2025)
Chapter one presented the concept of internal auditing, how internal auditing impacts financial performance, and the importance of effective internal audit functions in ensuring accurate financial reporting, mitigating financial risks, and overall influencing the economic health of an organization. In this chapter, the study will be based on specific objectives. These include to examine the different internal audit attributes used by an organization, to find out challenges internal auditors face when doing auditing duty and to find out the effect of internal audit and corruption among auditors in an organisation, that shall be able to guide the investigation and enhance clarity in terms of communication about research goals and expected outcomes. Chapter two also provided a comprehensive review of the literature on the effects of monetary rewards, promotion, and recognition on employee performance. The review covers key concepts, theories, and empirical findings related to the independent variable (internal auditing) and the dependent variable (financial performance). The chapter also identifies gaps in the current literature and highlights the significance of the proposed study by synthesizing the findings of these studies. This chapter aims to identify the key factors that influence employee performance and inform the development of evidence-based management practices Chapter three examines the study design, the area and population of the study, sample size and selection, specimen procedure and techniques, data collection methods and instruments, quality control measures, procedure of data collection, analysis of data, and measurement of the variables of the study. It also points out the ethical issues to be observed in the study. Chapter four consisted of data presentation, analysis, and interpretation of the findings on the themes of the study Chapter five presented the summary of the findings, conclusion, and recommendations of the study, and in the long run, the further areas of study.
Undergraduate